Omega-3 Fatty Acids Supplementation Improve Nutritional Status and Inflammatory Response in Patients With Lung Cancer: A Randomized Clinical Trial - Cheng, Mingjin; Zhang, Shengqiang; Ning, Chengdong; Huo, Qianlun (Frontiers in Nutrition, 2021)
Background & aims: Clinical studies have reported positive results with omega-3 supplements in oncologic patients. The aim of this study was to evaluate the efficacy of Omega-3 fatty acids supplementation in improving the nutritional status and inflammatory markers of patients with lung cancer. Methods: In a randomized double-blind parallel design trial, sixty patients with lung cancer at nutritional status risk based on Nutrition Risk Screening 2002 were randomized to be allocated to two study groups, receiving omega 3 fatty acids supplement (EPA 1.6 g and DHA 0.8 g) or placebo for 12 weeks. Anthropometric measurements (weight, BMI, upper-arm circumference, and triceps skinfold thickness), nutritional-based laboratory indices (hemoglobin, albumin, triglyceride, cholesterol), and inflammatory markers (CRP, TNF alpha, and IL-6) were measured before and after the intervention as study outcomes. Results: No significant difference between the two study groups were observed regarding basic characteristics and study outcomes. Compared with placebo group, omega-3 fatty acids supplementation group showed significant higher weight (66.71±9.17 vs 61.33±8.03, p= 0.021), albumin (4.74±0.80 vs 4.21±0.77, p= 0.013), and triglyceride (130.90±25.17 vs 119.07±14.44, p= 0.032). Inflammatory markers were significantly reduced in omega-3 group compared to placebo (CRP 1.42±0.63 vs 3.00±1.05, p= 0.001 and TNFα 1.92±0.65 vs 4.24±1.19, p= 0.001). No significant difference was observed between the two study groups regarding changes in BMI, arm circumference, and triceps skinfold thickness, triglyceride, cholesterol, and IL-6 (p>0.05). Conclusion: Omega-3 fatty acids supplementation can improve nutritional status and suppress the systemic inflammatory response in patients with lung cancer.